2006
DOI: 10.1143/jjap.45.4493
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties and Depolarization Temperature of (Bi1/2Na1/2)TiO3–(Bi1/2K1/2)TiO3 Lead-free Piezoelectric Ceramics

Abstract: The piezoelectric properties of a solid solution of the binary system, x(Bi 1=2 Na 1=2 )TiOx ¼ 0:50 { 0:98] were investigated, focusing on depolarization temperature, T d . Fine piezoelectric properties in lead-free piezoelectric ceramics were obtained near the morphotropic phase boundary (MPB) composition between the rhombohedral and tetragonal structures, and the highest electromechanical coupling factor, k 33 , and piezoelectric constant, d 33 , were 0.56 for BNKT84 and 157 pC/N for BNKT80, respectively. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
193
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(208 citation statements)
references
References 16 publications
14
193
1
Order By: Relevance
“…The existence of an MPB between (Bi 1/2 Na 1/2 )TiO 3 and (Bi 1/2 K 1/2 )TiO 3 in the compositional range 16-20 mol% (Bi 1/2 K 1/2 )TiO 3 was later substantiated by Sasaki et al [57] based on structural studies indicating coexistence of rhombohedral and tetragonal phases as well as the corresponding compositionally dependant peaks in the dielectric, piezoelectric and electromechanical coefficients. More recent studies [58][59][60][61][62][63] • C) is higher than that of pure (Bi 1/2 Na 1/2 )TiO 3 as expected, however, the depolarization temperature (due to a polymorphic phase transformation to the intermediate pseudocubic phase) is quite low reaching a minimum (T d = 140…”
Section: Bismuth Sodium Titanate-bismuth Potassium Titanate Solid Solsupporting
confidence: 52%
“…The existence of an MPB between (Bi 1/2 Na 1/2 )TiO 3 and (Bi 1/2 K 1/2 )TiO 3 in the compositional range 16-20 mol% (Bi 1/2 K 1/2 )TiO 3 was later substantiated by Sasaki et al [57] based on structural studies indicating coexistence of rhombohedral and tetragonal phases as well as the corresponding compositionally dependant peaks in the dielectric, piezoelectric and electromechanical coefficients. More recent studies [58][59][60][61][62][63] • C) is higher than that of pure (Bi 1/2 Na 1/2 )TiO 3 as expected, however, the depolarization temperature (due to a polymorphic phase transformation to the intermediate pseudocubic phase) is quite low reaching a minimum (T d = 140…”
Section: Bismuth Sodium Titanate-bismuth Potassium Titanate Solid Solsupporting
confidence: 52%
“…3,5 Nevertheless, one of the major drawbacks of these newly developed materials is the limited temperature regime in which the high performance is achieved. 2,4 For example, Bi 1/2 Na 1/2 TiO 3 -0.06BaTiO 3 (BNT-BT) loses piezoelectric properties around 100 C, 6 and Bi 1/2 Na 1/2 TiO 3 -0.2Bi 1/2 K 1/2 TiO 3 (BNT-BKT) has a similar polarization loss at $150 C. 7 K 0.5 Na 0.5 NbO 3 (KNN) shows a polymorphic phase transition (PPT) between orthorhombic and tetragonal structure at $200 C, above which the piezoelectric properties degrade. High performance in these lead-free ceramics is achieved by shifting the PPT to room temperature, which can be done by various dopants.…”
Section: Introductionmentioning
confidence: 99%
“…Takenaka et al have demonstrated that (Bi,Na)TiO 3 (BNT) is an attractive piezoelectric material 1)3) because it has a large spontaneous polarization. However, the piezoelectric properties of BNT are lost or drastically deteriorated above the depolarization temperature (T d ) at 200°C for BNT 4), 5) due to the structural phase transition from rhombohedral (R3c symmetry: ferroelectric) to tetragonal (P4bm symmetry: ferriferroelectric). 6) Recent investigations have focused on increasing the T d for solid solutions of BNT with other perovskite materials.…”
Section: Introductionmentioning
confidence: 99%